Fatal pulmonary thromboembolism associated with hemoglobin SC disease in a 15 year-old boy - Amancio, Thiago Trolez; Costa, Anderson da Costa Lino; Borsato, Marcela Longo; Marins, Leandro; Bacchi, Lívia Moscardi; Zerbini, Maria Claudia Nogueira (Autopsy and Case Reports, 2011)
We report a case of hemoglobin SC disease complicated by fatal pulmonarythromboembolism in a 15 year-old Brazilian boy, submitted to autopsy. Thiscase shows the importance of early diagnosis and treatment of sickle celldisease, which generates systemic involvement in youth and the importanceof considering the hypercoagulability in these patients. The autopsy was veryinstructive, revealing the florid morphologic aspect of sickle cell disease andits complications.